Scanning Quadrupole Data-Independent Acquisition, Part A: Qualitative and Quantitative Characterization - Moseley, M. Arthur; Hughes, Christopher J; Juvvadi, Praveen R; Soderblom, Erik J; Lennon, Sarah; Perkins, Simon R; Thompson, J. Will; Steinbach, William J; Geromanos, Scott J; Wildgoose, Jason; Langridge, James I; Richardson, Keith; et al. (Journal of proteome research, 2018)
A novel data-independent acquisition (DIA) method incorporating a scanning quadrupole in front of a collision cell and orthogonal acceleration time-of-flight mass analyzer is described. The method has been characterized for the qualitative and quantitative label-free proteomic analysis of complex biological samples. The principle of the scanning quadrupole DIA method is discussed, and analytical instrument characteristics, such as the quadrupole transmission width, scan/integration time, and chromatographic separation, have been optimized in relation to sample complexity for a number of different model proteomes of varying complexity and dynamic range including human plasma, cell lines, and bacteria. In addition, the technological merits over existing DIA approaches are described and contrasted. The qualitative and semiquantitative performance of the method is illustrated for the analysis of relatively simple protein digest mixtures and a well-characterized human cell line sample using untargeted and targeted search strategies. Finally, the results from a human cell line were compared against publicly available data that used similar chromatographic conditions but were acquired with DDA technology and alternative mass analyzer systems. Qualitative comparison showed excellent concordance of results with >90% overlap of the detected proteins.